DEVELOPMENT OF SELF-LEARNING MEDIA BASED ON ISPRING SUITE 10 ON RESPIRATORY SYSTEM MATERIALS IN CLASS XI-MIA IN METHODIST 8 MEDAN PRIVATE HIGH SCHOOL MEDAN - Irene M. Silaban; Mariaty Sipayung; Golarden Purba (UNIVERSITAS NEGERI MEDAN, 2023)
This study aims to determine the feasibility level of the Learning Multimedia that was developed based on the ispring suite 10 as a source of independent learning on the respiratory system material for class XI SMA. Learning Media developed based on expert validation, namely material experts, media experts and based on field tests to obtain responses and assessments by subject teachers, and students. This study uses a 4-D model of instructional development design by Thiagarajan which includes 4 stages, namely; define, design, develop, and disseminate which are limited to limited field tests and limited distribution to see the results of students' classical learning mastery. Research preparation begins in August 2021 and will be carried out in October 2021 – July 2022. The product trial was conducted at the Methodist 8 Medan Private High School. The results of the study indicate that the Learning Multimedia that has been developed is feasible to be used as a source of student self-study because it meets the eligibility criteria. Based on expert validation, the mean score was 4.40 or 88% (very feasible) from material experts. Meanwhile, media experts obtained a mean score of 4.62 or 92.4% (very feasible). Based on the results of field tests on teacher and student responses, it was obtained a mean score of 87.05 (very feasible) from the results of the teacher's assessment of the field of study and a mean score of 90.62 (very decent) from the results of student assessments. Students' classical learning completeness in limited distribution gets a percentage of 86.15% (very decent).